PENGARUH DANA PIHAK KETIGA, KEWAJIBAN PENYEDIAAN MODAL MINIMUM, NON PERFORMING FINANCING, RETURN ON ASSET, DAN LOAN TO ASSET RATIO TERHADAP PEMBIAYAAN (Studi Pada Bank Umum Syariah Yang Terdaftar Di Bank Indonesia Periode Tahun 2011-2015) - Khana Sae Mariya, 12.05.52.0139; Lisiantara, G. Anggana (Students' Journal of Accounting and Banking, 2016)
This study aims to examine and analyze the influence of third party funds, the capital adequacy ratio, non-performing financing, return on assets, and the loan to asset ratio against Islamic commercial bank financing in the period 2011-2015. The population in this study is an Islamic commercial bank (BUS) which operates in Indonesia from 2011 until 2015. This research is an empirical study by using purposive sampling technique of sampling. The analysis was performed by multiple regression using SPSS for windows version 19:00. The results showed that the Third Party Fund (DPK) has a significant positive effect on the distribution of funding. Capital Adequacy significant positive effect on financing. Non Performing Financing significant positive effect on financing. Return on assets of significant positive effect on financing. Loan to Assets Ratio (LAR) significant positive effect on financing.Keywords: Third Party Funds, Capital Adequacy, Non Performing Financing, Return on Assets, Loan to Asset Ratio and Financing